Management of School Facilities and Infrastructure as a Support for Extracuricular Activities at Junior High School 30 Semarang - Al Ayyubi, Shalahuddin; Abdullah, Shodiq (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
Schools have the function of providing guidance and development of all the potential of students, both in the form of physical, intellectual and moral potential. Therefore, schools provide physical and non-physical facilities, especially extracurricular activities. This study aims to analyze the management process of educational facilities and infrastructure in optimizing extracurricular activities.  This research is a qualitative study with data collection techniques by means of observation, interviews, and documentation. Data analysis was carried out by data reduction, data discussion, and conclusion drawing. The results of the study concluded that the management of facilities and infrastructure at Junior High School 30 Semarang includes planning, procurement, use, inventory, maintenance, and elimination. The process begins with planning needs, followed by procurement through an online shopping system according to Ministry of Education and Culture regulations. The use of facilities and infrastructure is supervised by the deputy head of facilities and infrastructure. Inventory is conducted regularly to reduce the risk of loss, while maintenance involves extracurricular parties in maintaining the condition of the facilities. Items that are not suitable will be removed according to the procedure. Supporting factors include the support of the school community, while inhibiting factors include teachers' workload and limited funds.